Die Frauenfrage in der Genossenschafts-Bewegung : ein Beitrag zum Genossenschaftswesen und zur moderenen Frauenbewegung - Schloesser, Robert, 1892- (Verbrauchergenossenschaftliche Bucherei, 1922)
The "Verein" of the 19th century seems in the early 20th century to have been replaced by the "Genossenschaft." This series of essays details not only the role of women in such associations, but concentrates in the main on the woman as organizer of the household and as consumer.